Difference in the Source of Anti-AQP4-IgG and Anti-MOG-IgG Antibodies in CSF in Patients With Neuromyelitis Optica Spectrum Disorder. (6th July 2021) - Akaishi, Tetsuya; Takahashi, Toshiyuki; Misu, Tatsuro; Kaneko, Kimihiko; Takai, Yoshiki; Nishiyama, Shuhei; Ogawa, Ryo; Fujimori, Juichi; Ishii, Tadashi; Aoki, Masashi; Fujihara, Kazuo; Nakashima, Ichiro
Abstract : Objective: To elucidate the differences in the source and in the level of intrathecal synthesis between anti–aquaporin-4 antibodies (AQP4-IgG) and anti-myelin oligodendrocyte glycoprotein antibodies (MOG-IgG). Methods: Thirty-eight patients with MOG-IgG–associated disease and 36 with AQP4-IgG–positive neuromyelitis optica spectrum disorders (NMOSD) were studied for the antibody titers in the sera and CSF simultaneously collected in the acute attacks. The quotients between CSF and serum levels of albumin, total immunoglobulin G, and each disease-specific antibody were calculated. Intrathecal production level in each disease-specific antibody was evaluated by calculating the antibody index from these quotients. Results: Eleven of the 38 patients with MOG-IgG were positive for the antibody only in the CSF, while no patient with AQP4-IgG showed CSF-restricted AQP4-IgG. Blood-brain barrier compromise as shown by raised albumin quotients was seen in 75.0% of MOG-IgG–positive cases and 43.8% of AQP4-IgG–positive cases. Moreover, MOG-IgG quotients were >10 times higher than AQP4-IgG quotients (effect size r = 0.659, p < 0.0001). Elevated antibody index (>4.0) was confirmed in 12 of 21 with MOG-IgG, whereas it was seen only in 1 of 16 with AQP4-IgG (φ = 0.528, p < 0.0001). The CSF MOG-IgG titers (ρ = 0.519, p = 0.001) and antibody indexes for MOG-IgG (ρ = 0.472, p = 0.036) correlated with the CSF cell counts but not with clinical disability. Conclusions: Intrathecal production of MOG-IgG may occur more frequently than that of AQP4-IgG. This finding implies the different properties of B-cell trafficking and antibody production between MOG-IgG–associated disease and AQP4-IgG–positive NMOSD.